GNSS spoofing in conflict zones disrupts wildlife tracking and hampers research and conservation efforts - Frédéric Jiguet; Asaf Mayrose; Markus Piha; Ron Efrat; Tuomas Seimola; Nir Sapir; Sami Timonen; Yohay Wasserlauf; Aurélien Besnard; Pierrick Bocher; Andrea Kölzsch; Aleksi Lehikoinen; et al. (Nature Communications, 2025)
In war and conflict zones, the jamming of Global Navigation Satellite System (GNNS) signals by military forces disrupts the tracking of tagged animals, and has increased in frequency following the recent escalation of conflicts in Eastern Europe and the Middle East. Such disruption to data collection strongly hampers research into the protection and conservation of endangered animals.